Undergraduate students' perception towards ward rounds as a clinical teaching strategy and perceived impact on academic performance in Zaria - Ladan, Muhammad Awwal; Musa, Halima Abdu; Aliyu, A.; Sani, D.K.; Adamu, Abdullah; Garba, S.; Lawal, Bilkisu Kankia; Ladan, Muhammad Fatimah (Nursing and Midwifery Council of Nigeria, 2016)
Background: The primary aim of this study is to assess the undergraduate students’ perception on ward-round and clinical teaching activities and its perceived impact on their academic performance in Ahmadu Bello University Teaching Hospital, Shika-Zaria. A descriptive survey design was employed as a methodology for the study. The study population includes undergraduate students of Bachelor of Nursing Sciences (BNSc) in 400 & 500L, Bachelor of Pharmaceutical Sciences (B.Pharm) in 500L and Bachelor of Medicine; Bachelor of Surgery (MBBS) in 400 & 500 Levels with a total number of 910.Materials and Methods: A cross sectional descriptive survey was employed as a study design. Structured questionnaire was used as instrument for data collection which was divided into five sections according to the objectives of the study. Results: The study population comprises of undergraduate students of Bachelor of Nursing Sciences (BNSc) in 400 & 500L, Bachelor of Pharmaceutical Sciences (B.Pharm) in 500L and Bachelor of Medicine; Bachelor of Surgery (MBBS) in 400 & 500 Levels. A sample size of 276 was used. Thef indings of the study revealed that, BNSc and MBBS students demonstrated good perception toward the concept of ward-round as clinical teaching strategy; B.Pharm students had good perception toward ward round but their clinical role was not clearly defined because of limited period of posting. Most of the students enjoyed participating in ward-round and they always participate. Among the BNSc students, “Team work” was rated most as an impact of ward-round that strongly influence their performance, while among the MBBS students “Work-based teaching” got the highest rating and B. Pharm students rated “Improved motivation” as an impact of ward-round that strongly influence their performance. Conclusion: It was concluded that undergraduate students demonstrated good perception of the concept of ward-round and they enjoy participating in all activities during clinical teaching. Interventions such as supervision and guidance of students’ activities while in the clinical area by the clinical instructors, increasing the number of postings of B. pharm students to the ward are needed for effective integration of learning.